Problem-based E-Book on Coffee Business Economic Activity Material in Social and Science Learning - Sutrisna, Sang Gede; Sujana, I Wayan; Ambara, Didith Pramunditya (Mimbar Ilmu, 2024)
Learning resources are essentially anything in the form of objects, data, facts, ideas, people, and so on that can foster the learning process. Learning activities in elementary schools are still monotonous and there is no innovation in learning resources. This study aims to prove the effectiveness of E-Book media based on Problem Based Learning on the material of coffee business economic activities in class science learning. This study is a type of development research that uses the ADDIE development model (analyze, design, development, implementation and evaluation). The subjects of this study were 25 fifth grade students. The method and instrument for data collection used multiple choice objective tests and questionnaires. The data analysis technique was descriptive quantitative and inferential statistics. The results of the study on the effectiveness of E-Books based on the results of the t-test obtained tcount = 14.06 for dk 48 and a significance level of 5% = 2.011. This means that tcount > ttable, so H0 is rejected and H1 is accepted. Thus, it can be concluded that this study shows that the development of E-Book construction based on Problem Based Learning material on coffee business economic activities in fifth grade social and science learning. The implications of this study are expected to be an example for teachers in implementing innovative learning.